STATUS PERWALIAN JANDA PASCA PERCERAIAN PERSPEKTIF HUKUM ISLAM DAN PERUNDANG-UNDANGAN DI INDONESIA - Ahmad Nur (Fakultas Syariah dan Hukum Islam Institut Agama Islam Negeri Bone, 2018)
Guardians are the legal requirement for marriage, both guardians for widows and girls. Jurists have agreed to this, except for the Hanafi group. This is based on differences in the way the Qur'an and Hadiths are interpreted. Whereas in the legislation in force in Indonesia, the guardian becomes the legal requirement for marriage. If the marriage is carried out without a guardian, the marriage is deemed null and void and the relationship is considered adultery. This was exposed in Article 26 of Law No. 1 of 1974 and Article 19-23 of the Compilation of Islamic Law.